1997
DOI: 10.5014/ajot.51.10.824
|View full text |Cite
|
Sign up to set email alerts
|

Forced Use of the Upper Extremity in Cerebral Palsy: A Single-Case Design

Abstract: Although the results of this single-case design are encouraging, further research with a randomized, controlled design is necessary to determine the effectiveness of the forced-use technique with a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 2 publications
0
60
2
1
Order By: Relevance
“…According to a recent Cochrane review, 2 CIMT and modified CIMT (mCIMT) should be distinguished from forced use therapy (FUT), which merely imposes a restraint on the unaffected upper limb. In the past few years, an increasing number of studies have indicated positive (m)CIMT effects on the potential of the affected arm to assist the unaffected arm during bimanual activities, 6,7 as well as on the quality, speed, and dexterity of upper limb function, [7][8][9][10][11][12][13][14][15] the spontaneous use of the affected arm, 8,9,11 and the level of independence in self-care. [7][8][9][12][13][14] However, the restraint method for the affected arm varied greatly (sling, splint, glove, cast), as well as the intensity and length of the restraint (from 8 hours daily during 2-3 weeks to 2 hours daily for 8 weeks).…”
Section: Constraint Induced Movement Therapy (Cimt)mentioning
confidence: 99%
“…According to a recent Cochrane review, 2 CIMT and modified CIMT (mCIMT) should be distinguished from forced use therapy (FUT), which merely imposes a restraint on the unaffected upper limb. In the past few years, an increasing number of studies have indicated positive (m)CIMT effects on the potential of the affected arm to assist the unaffected arm during bimanual activities, 6,7 as well as on the quality, speed, and dexterity of upper limb function, [7][8][9][10][11][12][13][14][15] the spontaneous use of the affected arm, 8,9,11 and the level of independence in self-care. [7][8][9][12][13][14] However, the restraint method for the affected arm varied greatly (sling, splint, glove, cast), as well as the intensity and length of the restraint (from 8 hours daily during 2-3 weeks to 2 hours daily for 8 weeks).…”
Section: Constraint Induced Movement Therapy (Cimt)mentioning
confidence: 99%
“…Only one study designated the length of time that a child exhibited hemiplegia as an inclusion criteria, i.e., chronic vs. acute (Willis et al, 2002). In addition, sensory integrity and/or amount of active movement in the involved wrist and hand were used to determine suitability for participation for children in six of the studies (Yasukawa et al, 1990;Crocker et al, 1997;Charles et al, 2001;Eliasson et al, 2003; (Taub & Wolf, 1997). Specifically, restraints that allow some use of the non-involved extremity will result in less intensive practice because the non-involved arm can still be used to complete tasks.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The following different types of restraints were used during the restraint period in the pediatric studies: casts (Yasukawa, 1990;Glover et al, 2002;Willis et al, 2002;DeLuca et al, 2003), resting splints (Crocker, 1997;Glover et al, 2002;Eliasson et al, 2003), slings (Charles et al, 2001;Charles et al, unpublished;unpublished), mitts (Pierce et al, 2002;Karman et al, 2003), and gentle intermittent physical restraint (Naylor & Bower, in press). Whereas each study described the extent of the restraint (usually by how much of the extremity was covered by the restraining device), few studies provided a rationale for employing a particular type of restraint.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Occupational therapy for children with CP 13 Multidisciplinary, outcome measures not included in review Case-Smith 22 Participants with CP and other diseases Colbert 23 Outcome measures not included in review Crawford 24 Outcome measures not included in review Damle 25 Outcome measures not included in review Fetters 26 Outcome measures not included in review Fisher 27 Participants with CP and other diseases Hankinson 28 Outcome measures not included in review Hasdai 29 Participants with CP and other diseases Hulme 30 Participants with CP and other diseases Hulme 31 Participants with CP and other diseases Manley 32 Outcome measures not included in review Palmer 33 Outcome measures not included in review Reid 34 Outcome measures not included in review Rennie 35 Participants with CP and other diseases Barnes 36 Single subject design Barnes 37 Single subject design Crocker 38 Single subject design Durfee 39 Single subject design Everson 40 Single subject design, outcome measures not included in review Goodman 41 Single subject design Hsieh 42 Single subject design Hulme 43 Single subject design, participants with CP and other diseases Kinghorn 44 Single subject design Lilly 45 Single subject design McCormack 46 Single subject design Reid 47 Single subject design Sakemiller 48 Single subject design Smiths 49 Single subject design Tona 50 Single subject design…”
Section: Appendix 1 -Criteria Of Methodological Qualitymentioning
confidence: 99%